Fabrication of 3D Photonic Crystals toward Arbitrary Manipulation of Photons in Three Dimensions - Kenji Ishizaki; Katsuyoshi Suzuki; Susumu Noda (Photonics, 2016)
The creation of large-area, unintentional-defect-free three-dimensional (3D) photonic crystals in the optical regime is a key challenge toward the realization of the arbitrary 3D manipulation of photons. In this article, we discuss an advanced fabrication method of 3D silicon photonic crystals based on the highly accurate alignment and wafer bonding of silicon-on-insulator (SOI) wafers. We introduce an advanced alignment system, in which the alignment process is automated by image recognition and feed-back control of stages, and show that it achieves an alignment accuracy better than ~50 nm. The bonding of SOI wafers is also investigated to obtain 3D crystals composed of highly pure crystalline silicon. We show the fabrication results of large-area 3D photonic crystals based on such considerations and demonstrate the successful introduction of artificial defects as functional components, such as coupled waveguide pairs or waveguides/nanocavities. We expect that these will be pioneering results toward the arbitrary 3D control of photons using 3D photonic crystals.